Khat chewing prevalence and correlates among university staff in Ethiopia: a cross-sectional study - Yeshaw, Yigizie (BMC Res Notes, 2019)
OBJECTIVES: Khat is an herbal cultivated plant growing mainly in Eastern Africa and Arabians. Chronic khat chewing leads to the development of liver toxicity, cardiovascular disease, sleeping disorder, psychosis, memory impairment, poor academic performance and variety of social and economic problems affecting the consumers and their families. Therefore, this study aimed to determine the prevalence of khat chewing and associated factors among Jimma university staff. An institution-based cross-sectional study was employed on 354 university staff. A self-administered questionnaire was used to collect the data. The analysis was done using Stata 14. A multivariable logistic regression model was used to identify associated factors of khat chewing among university staff. p ≤ 0.05 was employed to declare statistically significant factors. RESULTS: The lifetime prevalence of khat chewing among university staff was 41.0% (95% CI 35.9–46.1%). The odds of khat chewing was higher among males (AOR = 2.66 95%, CI 1.52–4.68), participants who had khat chewer friends (AOR = 2.15 95% CI 1.18–3.93), alcohol users (AOR = 9.02, 95% CI 4.96–16.42) and participants who had khat chewer family member (AOR = 4.03, 95% CI 1.16–13.99). Since a significant proportion of staff chew khat, appropriate measures need to be taken to reduce its prevalence and adverse social and health consequences.